Rapid determination of multi-antibiotic residues in honey based on modified QuEChERS method coupled with UPLC–MS/MS. (16th April 2022) - Yang, Yan; Lin, Guobing; Liu, Lijing; Lin, Tainan
Highlights: A multi-residue method was developed and validated for determination of 70 antibiotics in honey. A modified QuEChERS method combined with LC-MS/MS was optimized. The internal standards were used to obtain accurate quantification. Methacycline, oxytetracycline, tetracycline and metabolite 4-tetracycline were detected in honey. The method is time-saving, high-throughput and suitable for the monitoring of antibiotics residue in honey. Abstract: Antibiotic residues in honey cause public health problems. To analyze multi-antibiotic residues in honey, a modified QuEChERS (quick, easy, cheap, effective, rugged and safe) extraction method coupled with ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) was developed for simultaneous quantification of 70 antibiotic residues in honey. Matrix-matched calibrations indicated the correlation coefficients were higher than 0.998. The recovery was in a range of 70.5%-119.8% with intra-day relative standard deviation (RSD) of ≤ 10.0% and inter-day RSD of ≤ 13.9%. The limits of detection ranged between 0.050 μg/kg and 1.02 μg/kg. Limits of quantification was 0.17 μg/kg to 3.40 μg/kg. The matrix effects were negligible in 71.4% of compounds and moderately in 24.3% of compounds. Methacycline, oxytetracycline, tetracycline and its metabolite 4-tetracycline residues were detected in the tested samples. Validation parameters were acceptable and were in line with the Codex guidelines. This method was effective for detecting multi-antibiotic residues in honey.